2014
DOI: 10.1021/bi500149q
|View full text |Cite
|
Sign up to set email alerts
|

The Actin Binding Affinity of the Utrophin Tandem Calponin-Homology Domain Is Primarily Determined by Its N-Terminal Domain

Abstract: The structural determinants of the actin binding function of tandem calponin-homology (CH) domains are poorly understood, particularly the role of individual domains. We determined the actin binding affinity of isolated CH domains from human utrophin and compared them with the affinity of the full-length tandem CH domain. Traditional cosedimentation assays indicate that the C-terminal CH2 domain binds to F-actin much weaker than the full-length tandem CH domain. The N-terminal CH1 domain is less stable and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(66 citation statements)
references
References 33 publications
12
54
0
Order By: Relevance
“…We separately expressed the minimal CH1 and CH2 domains from utrophin fused to mCherry ( Fig S1). The isolated CH1 domain of utrophin had a high relative bound fraction (0.55±0.09, p*<0.05) ( Fig 1D), although the isolated domain appeared partially insoluble, aggregating within cells ( Fig S1 A,B), consistent with previous observations about its stability in vitro (Singh et al, 2014). The isolated CH2 domain was soluble but distributed throughout the cytosol (Fig S1 C) with a low relative bound fraction (-0.27±0.06, p****<0.05) ( Fig 1D), implying that it alone has minimal actin-binding activity.…”
Section: Measurement Of Ch1-ch2 Domain Binding In Vitro and In Live Csupporting
confidence: 90%
See 1 more Smart Citation
“…We separately expressed the minimal CH1 and CH2 domains from utrophin fused to mCherry ( Fig S1). The isolated CH1 domain of utrophin had a high relative bound fraction (0.55±0.09, p*<0.05) ( Fig 1D), although the isolated domain appeared partially insoluble, aggregating within cells ( Fig S1 A,B), consistent with previous observations about its stability in vitro (Singh et al, 2014). The isolated CH2 domain was soluble but distributed throughout the cytosol (Fig S1 C) with a low relative bound fraction (-0.27±0.06, p****<0.05) ( Fig 1D), implying that it alone has minimal actin-binding activity.…”
Section: Measurement Of Ch1-ch2 Domain Binding In Vitro and In Live Csupporting
confidence: 90%
“…An example showing the actin-binding domain of filamin A compared to utrophin ABD is given in Fig 1C. We first quantified the binding of CH1 and CH2 domains alone in live cells and compared to previous measurements of CH1 and CH2 affinity. Affinity of tandem CH1-CH2 domains for f-actin is known to primarily arise from the CH1 domain, as CH2 alone cannot bind to actin (Singh et al, 2014). We separately expressed the minimal CH1 and CH2 domains from utrophin fused to mCherry ( Fig S1).…”
Section: Measurement Of Ch1-ch2 Domain Binding In Vitro and In Live Cmentioning
confidence: 99%
“…The latter does not show much change in structure (movie SM3). The cross play between the two CH subdomains has recently been highlighted . Our study demonstrates how the switch between the open and the closed forms can be brought about by the interaction of residues across CH1 and CH2 subdomains in utrophin.…”
Section: Discussionmentioning
confidence: 66%
“…The cross play between the two CH subdomains has recently been highlighted. 49 Our study demonstrates how the switch between the open and the closed forms can be brought about by the interaction of residues across CH1 and CH2 subdomains in utrophin. The opening/closing of the dystrophin is caused by change in the helicity of the linker region.…”
Section: Discussionmentioning
confidence: 71%
“…But the situation may not be this simple. A recent study has found that the isolated utrophin CH1 domain has a similar binding affinity as the intact utrophin ABD (CH1 and CH2 domains) while the isolated utrophin CH2 domain shows only very weak binding 44 . The utrophin CH1 has both the ABS1 and ABS2 which is consistent with a requirement for the ABS2 for F-actin binding.…”
Section: Discussionmentioning
confidence: 99%